Gastroesophageal reflux disease (Proceedings of the Seventeenth Russian Gastroenterological Week, October 10–12 2011, Moscow) - I. V. Mayev; G. L. Yurenev; G. A. Busarova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To review publications on gastroesophageal reflux disease (GERD) with the accent on data of XVII Russian gastroenterological week, October 10–12, 2011.Original positions. GERD is one of the most actual problems of modern gastroenterology due to its high prevalence, frequent relapses, and significant deterioration of patients’ quality of life. Difficulties of recognition are quite often related to extraesophageal masks of disease. Delayed diagnostics of GERD and poor efficacy of proposed modes of treatment result in disease progression and development of such complications, as esophageal ulcerative bleeding, strictures of the esophagus, Barret's esophagus, development of adenocarcinoma.Conclusion. At the present stage there are many unresolved questions of etiopathogenesis, pathomorphology, diagnostics and treatment of GERD that requires further studies, improvement of diagnostics methods, development of new drugs and modes of treatment.